The Effect of Pineapple Juice on Perineal Wound Healing Among Post Partum Women - Shinta Novelia; Siti Syamsiah; Nia Kurnia (Nursing and Health Sciences Journal (NHSJ), 2023)
Perineal rupture is one of the causes of maternal morbidity and mortality during the post partum. The occurrence of infection can slow the healing of the perineal wound because the tissue that will grow into new tissue in the wound is damaged. Based on data, at Cimacan Hospital in June to August 2021 there were 105 cases of women who experienced perineal rupture during labor. This study aims to find out the Effect Pineapple Juice on The Healing of Perineal Wounds in post partum women at Cimacan Hospital. This study uses the design of Quasy Eksperiment with a postest only control group approach, by dividing two groups, namely the experimental group and the control group. The sample in this study amounted to 30 women with rupture consisting of 15 experimental groups and 15 control groups. Sample selection technique using total sampling. Research instruments consist of documentation, observation sheets as well as the REEDA scale. The data was analyzed using the Independent t test to determine the difference in influence between groups. The results showed that there was an influence on the healing of perineal wounds of the experimental group and the control group given pineapple juice and those that were not, with a significance value of 0.02 which means p<0.05. The preparation of pineapple has an effect on the healing of perineal wounds in women with rupture perineum. It is hoped that the results of this study can invite others to know the benefits of pineapple juice for perineal wound healing.